1999
DOI: 10.1021/ic990331g
|View full text |Cite
|
Sign up to set email alerts
|

A Cu(II)-Mediated C−H Oxygenation of Sterically Hindered Tripyridine Ligands To Form Triangular Cu(II)3 Complexes

Abstract: Two sterically hindered tris-pyridyl methane ligands, tris(6-methyl-2-pyridyl)methane (L1) and bis(6-methyl-2-pyridyl)pyridylmethane (L2), are newly synthesized. Under aerobic conditions, Ln (n = 1 or 2) reacts with CuX2 (X = Cl or Br), oxygenated at the methine position to LnOH or LnOMe. The former alcoholate ligand creates trinuclear Cu(II) complexes [Cu3(X)(LnO)3](PF6)2 [(X, n) = (Br, 1) 1, (C1, 1) 2, (Br, 2) 3, or (C1, 2) 4] in which the alkoxide oxygen atoms bridge copper centers. The crystal structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…Alkoxo‐bridged tricopper(II) clusters with similar [Cu 3 O 3 ] motifs are known, but generally form by self‐assembly of mononuclear copper(II) moieties 12a. 13 The magnetic behavior of these complexes has been studied because spin‐frustrated triangular complexes may exhibit interesting ground states.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkoxo‐bridged tricopper(II) clusters with similar [Cu 3 O 3 ] motifs are known, but generally form by self‐assembly of mononuclear copper(II) moieties 12a. 13 The magnetic behavior of these complexes has been studied because spin‐frustrated triangular complexes may exhibit interesting ground states.…”
Section: Methodsmentioning
confidence: 99%
“…13 The magnetic behavior of these complexes has been studied because spin‐frustrated triangular complexes may exhibit interesting ground states. It has been shown that varying the anion bridges of linear14 and triangular15 trinuclear copper(II) complexes changes the magnetic coupling, but no systematic study has been reported of these effects on μ‐alkoxo‐bridged trimers lacking a strongly μ 3 ‐coordinated ligand 12a. 16 Since the synthesis of anion variants of the tricopper(II) complexes supported by the trinucleating ligand L described above is facile, a magnetostructural investigation of the effect of the capping anion the [Cu 3 O 3 N 6 ] core was performed.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the 360 nm band suggests interaction of the free pyridyl groups with Fe, but the L 1 :Fe stoichiometry is not compatible with a binding of just a second Fe 2+ ion to the tris(pyrid-2yl) site in the interior of the cage. Rather, the OH group in L 2 might act as a bridging ligand {as observed for the Cu 2+ ions in the related complex [Cu 3 (Br)(L) 3 ](PF 6 ) 2 , [21] where L = tris(6-methyl-2-pyridyl)methanol}, for up to three Fe II ions with additional coordination by one pyridyl group each and located at the exterior of the cage. sharp signals increases and that of the broad signals decreases.…”
Section: Structure Of Tris(3-methyl-pyrid-2-yl)aminementioning
confidence: 99%
“…[64][65][66] We found that copper complexes with sterically hindered tripyridine ligands can be structurally modulated by introducing an alkyl group at the bridgehead position of the ligand. 67 We prepared three sterically hindered tripyridine ligands: tris-(6-methyl-2-pyridyl)methane (H6M3t), 68 1,1,1-tris(6-methyl-2-pyridyl)ethane (Me6M3t), 67 and 1,1,1-tris(6-methyl-2-pyridyl)propane (Et6M3t). 67 The chemical structures of H6M3t, Me6M3t, and Et6M3t are shown in Chart 4.…”
Section: Reversible O 2 -Binding Greatly Improved By Structural Modulmentioning
confidence: 99%